Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s00405-013-2724-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chirp versus click and tone pip stimulation for cervical vestibular evoked myogenic potentials

Abstract: The current study explored differences among cervical vestibular evoked myogenic potentials (cVEMP) that were evoked by CE-chirp and click and tone pip in healthy controls, and tried to explain the differences of cVEMP between the three of them. Thirty normal volunteers were used as subjects for CE-chirp and click and tone-pip (Blackman pip) stimuli. The latency of P1, N1, peak-to-peak P1-N1 amplitude, and cVEMP interaural difference were obtained and analyzed. The response rates of cVEMP were 93 % for click a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Wang et al compared the VEMP responses evoked by click stimuli with those evoked by tone pips in healthy young individuals and observed that the response rates of VEMP were 93 % for click and 100 % for tone pips. 9 In the present study, the initial response at around 13 ms latency was positive wave followed by a negative wave at around 23 ms. This initial response was because of the placement of the electrodes.…”
Section: Resultssupporting
confidence: 50%
“…Wang et al compared the VEMP responses evoked by click stimuli with those evoked by tone pips in healthy young individuals and observed that the response rates of VEMP were 93 % for click and 100 % for tone pips. 9 In the present study, the initial response at around 13 ms latency was positive wave followed by a negative wave at around 23 ms. This initial response was because of the placement of the electrodes.…”
Section: Resultssupporting
confidence: 50%
“…Compatible with current literature, our study found that the tone burst stimulation resulted in statistically significantly higher P13-N23 amplitudes than other stimulus types. To the best of our knowledge, there is only one study comparing chirp stimulus [9] . Wang and colleagues suggested that chirp stimulus demonstrates shorter latencies and increased speed and reliability.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier studies have used chirps of different bands-200-10,000Hz by Wang et al (6); 500-4000Hz by Özgür et al (7) and 250-1000Hz by Walther et al (8). All these studies compared the c-VEMP responses of chirp with clicks and 500 Hz tone bursts.…”
Section: Tablementioning
confidence: 99%
“…In 2010, Elberling et al (5) developed octave band chirps to be used to elicit ABRs. After 20 years since c-VEMP was first described, Wang et al (6) compared the c-VEMP responses using Chirps (200-10,000Hz), also called as CE-Chirps, Clicks and tone bursts. Özgür et al (Özgür et al, 2015) used narrowband chirps (500-4000Hz) and compared it with clicks and Tone bursts.…”
Section: Introductionmentioning
confidence: 99%